Genome Informatics 2009:Genome Informatics Series Vol. 22 - Edda Klipp (Genome Informatics Series, 2010)
This volume contains 17 peer-reviewed papers based on the presentations at the 9th Annual International Workshop on Bioinformatics and Systems Biology (IBSB 2009) held at the Life Science Engineering Building of Boston University from July 27 to 29, 2009. This workshop started in 2001 as a platform for doctoral students and young researchers to present and discuss their research results and approaches in bioinformatics and systems biology. It is part of a collaborative educational program involving leading institutions and leaders committed to the following institutions and programs: Boston University Graduate Program in Bioinformatics Charité - Universitätsmedizin Berlin Freie Universität Berlin Global COE Program - Center of Education and Research for Advanced Genome-Based Medicine, University of Tokyo The International Research Training Group (IRTG) Genomics and Systems Biology of Molecular Networks International Research and Training Program on Bioinformatics and Systems Biology, Kyoto University Bioinformatics Center Max-Delbrück Center for Molecular Medicine in Berlin Max Planck Institute for Molecular Genetics in Berlin Max Planck Institute of Molecular Plant Physiology in Potsdam